Abstracts of theses and dissertations on Philippine mass communication, 1974-1980 - De Jesus, Emilinda Villanueva 1939- (1982)
Based on the results of a survey of mass communication courses offered in larger colleges and universities in Metro Manila, a bibliographic search for theses dealing on all aspects of communication was conducted utilizing available library catalogs, bibliographies and indexes of the selected institutions, as well as the records of its graduate schools and research/publications offices.
The bibliography follows a simple subject arrangement with indices by author, title, institution and date. The entries are arranged alphabetically by author under each of the 25 broad subject categories which were adopted from the Bibliographic Publication Series of the Asian Mass Communication Research and Information Center (AMIC).
The compilation includes a total of 590 entries of which 511 are master's theses and 79 entries are doctoral theses. An abstract was provided for each of the theses to reflect not only their objectives, methodology and findings but also the extent and nature of communication research activities being undertaken by the institutions.
This study attempts to compile an abstract-bibliography of theses and dissertations on Philippine mass communication submitted to selected academic institutions from 1974 to 1980.
Mimeographed.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: Mass media -- Philippines -- Bibliography; Communication -- Philippines -- Bibliography